2016
DOI: 10.1190/geo2015-0305.1
|View full text |Cite
|
Sign up to set email alerts
|

Reducing high-frequency ghost cavitation signals from marine air-gun arrays

Abstract: Ghost cavitation, which is a term describing that cavitation bubbles are generated acoustically, has been hypothesized to occur when the ghost reflected signals from many individual air guns beneath the sea surface produce a pressure that is close to zero in the water above the source array. Ghost cavitation is typically observed some milliseconds after the ghost reflection, and it may last for 5-15 ms, depending on the configuration of the source array. The cavitation process subsequently generates a weak hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…This phenomenon was first hypothesized by recording high frequency (> 10 kHz) signals in a seismic air-gun array field measurement (Landrø et al, 2011). It was further analysed (Landrø et al, 2013) and investigated based on a dedicated field experiment (Landrø et al, 2016). The ghost cavitation phenomenon in an air-gun array was numerically modelled and could successfully predict the recorded highfrequency ghost cavitation signals and the associated low-frequency component (Khodabandeloo and Landrø, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was first hypothesized by recording high frequency (> 10 kHz) signals in a seismic air-gun array field measurement (Landrø et al, 2011). It was further analysed (Landrø et al, 2013) and investigated based on a dedicated field experiment (Landrø et al, 2016). The ghost cavitation phenomenon in an air-gun array was numerically modelled and could successfully predict the recorded highfrequency ghost cavitation signals and the associated low-frequency component (Khodabandeloo and Landrø, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Coste et al (2014) showed that the high-frequency signal generated by a single air gun can be reduced by approximately 10 dB for the frequency range between 0.5 to 3 kHz by implementing a new air gun design. The environmental aspects related to the highfrequency signal generated by air gun arrays have been discussed by several authors, see for example Coste et al (2014) and Landrø et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…When we apply a 5-10 kHz bandpass filter (Figure 3d), we observe that the high-frequency signal occurs at a much later time: around 94.5 ms for the near-offset trace and 97.5 ms for the far-offset trace. In this case, we attribute the major part of the signal to be caused by the ghost cavitation effect (Landrø et al, , 2013(Landrø et al, and 2016. The time shift of 3 ms between the near-and far-offset trace indicates that there is a shift between the onset of the source signature for the near and far offset and the maximum peak amplitude.…”
Section: Range Of the High-frequency Signalmentioning
confidence: 99%
See 2 more Smart Citations